Electron localization in mixed-valence manganites - COEY, JOHN MICHAEL DAVID (American Physical Society, 1995)
Mixed-valence manganites (A3+0.7B2+0.3)MnO3 exhibit a resistivity peak with giant negative magnetoresistance below the Curie point. Residual resistivity ranges from 5?10-8 to 8?103 m, but the electronic heat capacity when A=Y or La is that of a normal d-band metal; 6 mJ mole-1K-2. Spatial fluctuations in the Coulomb and spin-dependent potentials localize the eg(*) electrons in wave packets that are large on the scale of the Mn-Mn separation. Transport in the magnetically localized state involves zero-point-energy assisted hopping or tunneling of electrons from one weakly localized wave packet to another.
PUBLISHED
Keywords: Physics